Force Simulation for Junior School Physics - Muchammad Chusnan Aprianto (LPPM, Sekolah Tinggi Teknologi DR. KHEZ Muttaqien, 2019)
Gravitation is a primary subject in junior high school. The concept introducing gravitational acceleration, gravitational force, potential energy of gravitation, and planetary motion cause by gravitation. This paper will describe the use of simulation on general gravitation’s topic for junior high school physics. Planetary gravitation was selected as the topic of this simulation. The result shows that using simulation will increase student understanding in learning physics especially gravitation.